Body roundness index is related to the low estimated glomerular filtration rate in Chinese population: A cross-sectional study - Zhang, Yue; Gao, Wenxing; Ren, Rui; Liu, Yang; Li, Binqi; Wang, Anping; Tang, Xulei; Yan, Li; Luo, Zuojie; Qin, Guijun; Chen, Lulu; Wan, Qin; et al. (Frontiers in Endocrinology, 2023)
Background: Kidney disease is related to visceral obesity. As a new indicator of obesity, body roundness index (BRI) has not been fully revealed with kidney disease. This study's objective is to assess the relationship between estimated glomerular filtration rate (eGFR) and BRI among the Chinese population. Methods: This study enrolled 36,784 members over the age of 40, they were from 7 centers in China by using a random sampling method. BRI was computed using height and waist circumference, eGFR ≤ 90 mL/min/1.73 m2 was considered to indicate low eGFR. To lessen bias, propensity score matching was employed, multiple logistic regression models were utilized to examine the connection between low eGFR and BRI. Results: The age, diabetes and coronary heart disease rates, fasting blood glucose, and triglycerides were all greater in participants with low eGFR. The BRI quartile was still positively connected with low eGFR after controlling for confounding variables, according to multivariate logistic regression analysis. (OR [95%CI] Q2:1.052 [1.021-1.091], OR [95%CI] Q3:1.189 [1.062-1.284], OR [95%CI] Q4:1.283 [1.181-1.394], P trend < 0.001). Stratified research revealed that the elders, women, habitual smokers, and those with a history of diabetes or hypertension experienced the connection between BRI level and low eGFR. According to ROC, BRI was able to detect low eGFR more accurately. Conclusions: Low eGFR in the Chinese community is positively connected with BRI, which has the potential to be used as an effective indicator for screening kidney disease to identify high-risk groups and take appropriate measures to prevent subsequent complications.